Emotional factors relating to weight gain during the COVID-19 pandemic at post-bariatric women from São Paulo: a cross-sectional study - Victória Lacera Auerswald Albino, Anny; Rheded Ferreira, Glenda; da Silva Lima, Kaline; Matsuda de Sales Vieira , Larissa; Farah Simony Lamigueiro Toimil, Rosana; Riyoiti Uchida, Ricardo; Eduardo Nunes Salles, João (Seven Editora, 2023)
Objective: Evaluate the impact of the covid-19 pandemic on weight regain in post-bariatric women and correlate it with symptoms of anxiety, depression, binge eating, and fear of covid-19. Methods: It collected anthropometric and mental health information with the application of psychometric scales on the patients mentioned above, between May/2021 and January/2022. Frequencies (descriptive statistics), test t for independent samples, and Spearman were used to obtain a correlation between weight gain and the psychometric scales. Results: The sample comprised 25 women. The average age was 53.0 years and the average body mass index was 35.2kg/m2 before the pandemic. We observed an average increase in the body mass index of 1.4 points during the pandemic. However, 40% maintained or lost weight during the same period. The weight gain group had higher scores for depression, anxiety, and binge eating symptoms. Fear of covid-19 scores did not differ between the groups. Conclusion: Anxiety, depression, and binge eating symptoms have influenced weight to regain in a small sample of post-bariatric women during the covid-19 pandemic. DOI: https://doi.org/10.56238/devopinterscie-112